Biodiversity of Bees (Hymenoptera: Apoidea: Anthophila) in Connecticut (USA) - Zarrillo, Tracy A.; Stoner, Kimberly A.; Ascher, John S. (Zootaxa, 2025)
In response to calls for national and regional updated inventories of bee species, we present a county-level checklist for 385 confirmed bee (Apoidea: Anthophila) species for Connecticut, USA, highlighting rare and regionally declining species, species that have specific habitat and/or host requirements, and species whose taxonomy and distribution we wish to clarify. We have compiled a comprehensive, digitized database of historic and current bee records from Connecticut to inform this checklist, which includes specimen records from museums, recent collections, and community science observations from iNaturalist.com. All images of bees from Connecticut on iNaturalist (18,471 observations) have been fully vetted by one or more of the authors, which is unprecedented for a state project. We summarize historical bee research in Connecticut and provide current information regarding the distribution of bee species, changes in status, phenology, habitat usage, and floral associations within the state. At least 43 of 385 species represented in collections or literature have not been detected in Connecticut since the year 2000. These and other species of conservation concern are discussed with reference to a quantitative assessment of changes in range within the state. In addition, we have calculated and report state-level ranks for 124 bee species in Connecticut. We corroborate regional loss of species including Coelioxys funerarius Smith and Holcopasites illinoiensis (Robertson) and clarify and extend the distribution of numerous bee species in the Northeastern United States. Furthermore, we discuss morphospecies, excluded species, and species expected for Connecticut. We also validate synonymies reported previously online based on an unpublished manuscript by Roy Snelling for the following species: Nomada depressa Cresson (= N. hoodiana Cockerell; = N. carinicauda Cockerell; = N. media Mitchell); Nomada obliterata Cresson (= N. decepta Mitchell); Nomada vicina Cresson (= N. beulahensis Cockerell; = N. vicina stevensi Swenk). In addition, we recognize three new synonyms of Nomada xanthura Cockerell (= N. ochlerata Mitchell; = N. detrita Mitchell; = N. mendica Mitchell) and report the first Nomada townesi Mitchell from outside of Maryland. In addition to N. townesi, the following eleven native species are newly reported or recently confirmed for Connecticut: Andrena (Cnemidandrena) parnassiae Cockerell; Andrena (Melandrena) sayi Robertson; Andrena (Trachandrena) rehni Viereck; Anthophora bomboides Kirby; Nomada armatella Cockerell; Nomada electella Cockerell; Nomada placida Cresson; Lasioglossum (Dialictus) cattellae (Ellis); Lasioglossum (Dialictus) ellisiae (Sandhouse); Lasioglossum (Dialictus) fattigi (Mitchell); Lasioglossum (Dialictus) trigeminum Gibbs. The following recent arrivals among non-native species are confirmed: Pseudoanthidium (Pseudoanthidium) nanum (Mocsáry); Coelioxys (Allocoelioxys) coturnix Pérez; Osmia (Osmia) taurus Smith. This work is a stepping stone towards a larger, ongoing effort to clarify bee distribution and status in New England. As such, we also report updates for the bee fauna of the following states: Massachusetts—Melissodes communis communis Cresson; Megachile (Eutricharaea) apicalis Spinola), Maine—Chelostoma philadelphi (Robertson), and New Hampshire—Lasioglossum nelumbonis (Robertson).